Volatility Spillover Effect between Stock and Exchange Rate in Oil Exporting Countries - Mikhaylov, Alexey Yurievich (International Journal of Energy Economics and Policy, 2018)
This paper proposes the volatility spillover effect between stock and foreign exchange markets in both directions in oil exporting countries – Russia and Brazil. The data sample consists of daily observations. The method is based on FIGARCH model of the long memory. For emerging markets, volatility spillover is observed mainly in one direction: from the currency market to stock market. Calculations show that long memory is present in the dynamics of volatility, when models take into account structural breaks and frictions. We develop a model to predict the impact of oil prices on stock market indices for Russia, Brazil. The volatility spillover effect is observed in one direction: from the exchange rate to stock market. Calculations show that long memory is present in the dynamics of volatility, when models take into account structural breaks and frictions. This paper focuses on new method for forecasting of volatility (taking into account the structural breaks) on the base of FIGARCH model. The financial markets became more integrated after the World Economic Crisis of 2008-2009. The paper shows that volatility can be predicted using the FIGARCH model if the structural breaks are incorporated in the model. The paper should be of interest to readers in the areas of economic forecasting on the base of long memory models. Keywords: Efficient market hypothesis, stock indexes, exchange rates, FIGARCH model, structural breaks. JEL Classifications: C51, C58, F31, G12, G15